Customer Loyalty and Relationship Marketing in the Nepalese Telecommunications Sector - Sharma, Bhanu Bhakta; Shahi, Bhupendra Jung; Dahal, Rewan Kumar (The Harvest, 2023)
RM (Relationship Marketing) and CL (Customer Loyalty) have attracted a great deal of academic and professional attention over the past few decades. RM became a key trend in the marketing and management industries. Mobile communications networks have been a prominent infrastructure driving substantial economic growth in developing countries like Nepal. This study investigated CRM (Customer Relationship Marketing) and CL in the telecommunication industry in Nepal. A descriptive and causal-comparative research design has been adopted for this study as it seeks to identify the key variables of CRM and CL in the telecommunication industry in Nepal. Using survey methods, structured questionnaires with a five-point Likert scale on each dependent and independent variable were administered to obtain responses from mobile users. In this study, quantitative techniques have been used to analyze primary data collected through a survey. This study found a positive relationship between CL and its variables trust, communication, commitment, and conflict handling. Trust and commitment were the primary factors of CL in RM in the Nepalese telecom industry, with varied effects according to the measures of CL.